A Closer Look at Bioethics in the Curriculum: A Study on the Knowledge, Attitude, and Perception of Bioethical Principles Among Nursing Students - Tuquib, Buddy Jeson; Taja-on, Evan P. (PT FORMOSA CENDEKIA GLOBAL, 2025)
Understanding how nursing students learn and respond to ethical principles in healthcare helps reveal how well they are being prepared for real-life clinical decisions. Responses were gathered through an online survey completed over a three-week period involving 72 nursing students enrolled in the course Bioethics. The results show that nursing students possess a strong understanding of bioethical principles, hold a generally positive attitude, and recognize the real-life relevance of ethics in nursing practice. These findings suggest that integrating bioethics into the curriculum effectively supports the development of ethical awareness and decision-making among future healthcare professionals. The results underscore the importance of strengthening ethics education to ensure that nursing students are equipped to respond ethically and responsibly in diverse clinical settings.